دور الهندسة المالية في تفعيل الصيرفية الإسلامية - شوكة أحلام, غطاطا زهور (My University, 2022)
Due to the developments witnessed by Islamic banking and the achievement of many goals, many traditional banks have resorted to following the approach of Islamic law, this is done by opening independent windows within banks or by total transformation into Islamic banks, and This was welcomed by the Islamic communityfor is due to his desire not to violate the law. In response to the requirements imposed by economic changes, Islamic financial institutions seek to develop their industry by creating financial products that embody the image of the Islamic economy, this is through the adoption of Islamic financial engineering, which is considered to be the innovation of new financial tools and investment formulas that combine legitimate credibility and economic efficiency. Islamic financial engineering plays an important role in the development of the Islamic financial industry as a means of innovation and development.Therefore, its application in Islamic banks helps them to create alternativeIslamic financial tools for traditional products. Despite the weakness of Islamic financial institutions in Algeria, they are struggling to develop and increase and Al Baraka Bank was previously in this field. As it raised the ceiling of its challenges by adopting financial engineering in order to improve the quality of its products and meet the desires of its customers.Although, it still suffers from many problems and obstacles, so it is working hard to overcome it all.
دراسة حالة بنك البركة الجزائري
Keywords: financial engineering, islamic financial engineering, banking, islamic banks